Improving the detection and treatment of schizophrenia. - Giannopoulos, P; Carroll, A; Ebmeier, K (2014)
Schizophrenia is a debilitating, often chronic, psychotic disorder with early onset and a lifetime prevalence of 7.2/1,000. The longer the period without treatment, the worse the outcome. In the UK, the mean duration of untreated psychosis is one to two years. The new NICE guidelines for schizophrenia recommend that all patients who are distressed and have a decline in social functioning accompanied by psychotic symptoms or behaviour suggesting psychosis should be comprehensively assessed by a specialist mental health service. Antipsychotic medication remains the cornerstone of treatment in schizophrenia for the acute and the stabilisation-maintenance phase. The NICE guidelines recommend the use of psychological, social, occupational and educational interventions early in treatment. Mortality rates in schizophrenia are high and the majority of premature deaths are accounted for by physical illnesses. These include cardiovascular disease, diabetes mellitus, COPD, certain cancers and infectious diseases e.g. HIV, hepatitis C, and tuberculosis. Primary care has a significant role to play in monitoring mental state and physical health. Monitoring mental state is crucial. When relapse is threatened because of poor response to treatment, non-adherence to medication, intolerable side effects from medication, comorbid substance misuse, or if risk to self or others is suspected, GPs should refer the patient to the mental health team. GPs should provide a comprehensive health check yearly or more often if there is an indication.